Transporte, transmissibilidade e patogenicidade da micoflora associada às sementes de feijão (Phaseolus vulgaris L.) - SANTOS, GIL RODRIGUES DOS; COSTA, HÉLCIO; PELUZIO, JOENES MUCCIO; MIRANDA, GLAUCO VIEIRA (Revista Ceres, 2015)
.